MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF DENGAN PENERAPAN PENDEKATAN SETS - Sri Mulyaningasih, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2010)
Critical  and creative thinking is a cognitive development that is expected to have the students after the learning process takes place. Natural Sciences is a very broad knowledge and consists of several related disciplines. To learn not just rely on rote just because science is integrated with the knowledge of Science, Environment, Technology) and Society  or can be abbreviated by SETS is one approach that can motivate students in learning activities to think critically and creatively. This activity is carried out on teachers Junior High Schools in Surabaya northern incorporated in MGMP as much as  32 teachers. Implementation process is carried out: The first meeting discussions device (curriculum, materials and activity analysis), followed by a second meeting to presentation of group work as real teaching in class in accordance with the selected model teacher. From observations and questionnaires obtained show that: 8 teachers expressed very pleased with SETS approach, students are very interested because there is discussion time among friends, presentation of results and reflection. In the presentation of performance results of students who appear to think critically and creatively in its displays SETS. Conclusion: 1) SETS approach can be used as an alternative in teaching Science-2) Science can not be separated from the environment, technology, and society.